Treatment of textile effluents by the heterogeneous Fenton process in a continuous packed-bed reactor using Fe/activated carbon as catalyst - Filipa Duarte (2013)
This work deals with the treatment of textile effluents by the heterogeneous Fenton-like process in afixed-bed reactor filled with a catalyst based on activated carbon impregnated with iron (AC/Fe). In a preliminary stage, the dye Alcian Blue-tetrakis (methylpyridinium) was used as model compound. The catalyst is essentially microporous, with large micropores and some mesopores, and is able to adsorb thedye, although its adsorption capacity is limited as a consequence of the large size of the dye molecule.The stability of the catalyst was checked with five consecutive runs, without significant loss of activity(less than 5%). Then, the effect of the main operating conditions was analyzed, and the H2O2 dose, pHand temperature were optimized; the best conditions found using CAB,feed = 0.01 mM and a contact timeof 3.3 g min ml1 were: CH2O2,feed = 30.0 mM, pH = 2.5 and T = 50 C, with which it was achieved 93.2% ofdiscoloration and 54.1% of total organic carbon (TOC) removal in the steady-state. It was verified that pHhad a preponderant effect on the oxidation performance. Finally, the selected catalytic system wasapplied to the treatment of a real textile effluent used in the cotton dyeing. It was achieved almost totaldiscoloration (96.7%) and a strong abatement of the TOC - 73.6%, as well as of the chemical oxygendemand (COD) - 66.3%, and biochemical oxygen demand (BOD5) - 72.5%. The iron leached reached verylow levels in every run, which is a crucial factor for the catalyst long-term use